Ibn Sina on Happiness - Ali Shirvani (اخلاق وحیانی)
For Ibn Sina, happiness is the highest thing that the alive creature endeavor to find it. According to his ontological and anthropological principles, he regards the reason as the basic substance of human being, which by communicating with the active intellect and reaching the level of acquired intellect reaches to its final perfection and true happiness and benefits the highest and longest pleasure. In this paper, after explaining and analyzing Ibn Sina’s view about happiness, we will criticize it. Neglecting some of the existential realms of human being and happiness components, inconsistency with philosophical principles, neglecting the role played by faith and good deeds in human beings’ happiness and the lack of any separation between the happiness of individuals and the humankind, among others, are the deficiencies of Ibn Sina’s view.